Relationship between writing attitude and spelling capabilities in fourth and fifth grade students - Leable, Viviana (My University, 2014)
Struggling writers experience difficulty with spelling which can interfere with composing during writing. Spelling can influence their perceptions about their ability as a writer, thus affecting their attitudes about writing. This action research study examined the relationship between attitude about writing and spelling capabilities in fourth- and fifth-grade students with special needs. Self-regulated strategy development (SRSD) is an instructional approach that utilizes explicit, interactive, and scaffolded instruction to assist students with writing challenges to develop writing and self-regulation strategies. SRSD was used in this study to increase the use of efficient spelling strategies to assist with increasing the students' motivation and ability to write to be able to form a positive writing attitude. Results indicated that attitude about writing was not linked to a child's motivation and ability to produce text that is spelled correctly, because of each child overestimating his or her ability. Therefore, further research should be warranted in finding reasons for children overestimating their writing ability, as well as finding a tool or method to effectively evaluate a child's attitude.
Plan B Paper. 2014. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 39 leaves. Includes bibliographical references (leaves 34-39).
Keywords: English language--Writing-Study and teaching (Elementary); English language--Orthography and spelling-Study and teaching (Elementary); Self-efficacy; Learning disabled children--Education